Avaliação da qualidade da água do arroio mangueirão em Caçapava do Sul, RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Water is an abundant renewable natural resource, occupying 70% of the area in our planet, however 97% of this water is salty and cannot be consumed. Thus, only 3% of the water is fresh, and of this total, most of it is found in the glaciers and in the condition of groundwater. There remains 0.04% of available water on the surface, located in rivers, lakes and streams. If the small amount of water available were not enough, much of it is polluted due to human activities, such as discharge of domestic and industrial sewage, mining activities and urban drainage. This happens in big urban centres surrounding river areas. The Mangueirão river is located in the municipality of Caçapava do Sul, nearby the highway BR392, flowing through small villages and limestone factories with intense mining activities. Hence, the aim of this study is to survey the water quality of the Mangueirão river by means of biological and physiochemical parameters. Moreover, spectrophotometric analysis of aluminium and cadmium metals, using an approach based on CONAMA resolution No. 357 (2005) will be performed. All analyses will be carried out in the laboratories of the Federal University of Pampa, at the campus Caçapava do Sul.
Keywords: Recursos hídricos; Monitoramento ambiental; Poluição hídrica; Water resources; Environmental monitoring; Water pollution; CNPQ::CIENCIAS EXATAS E DA TERRA